(untitled) (IITM Journal of Business Studies, 2024)
The glass ceiling in higher educational institutions is a significant roadblock to sustainable development. Despite the increasing number of women in faculty positions, their career progression appears to be slow, with many remaining concentrated toward entry-level positions. This invisible barrier hinders women’s advancement to top positions, such as heads, deans, and directors. A study of 98 faculty members working in higher education sector in NCR region revealed that gender and psychological constraints were the strongest glass ceiling barriers. Other factors like perceived discrimination and a male dominating culture significantly determine the glass ceiling effect. The conceptual model of the glass ceiling and career development in the study highlights the complexities that hinder women’s career advancement. It offers a framework for thoroughly analyzing and addressing these issues, considering the interplay of societal, organizational, human, and external factors, as well as the importance of intersectionality and continuous adaptability. The study points out that this vertical segregation not only impedes individual career development but also undermines the broader goal of gender equality, a key aspect of sustainable development.